Pengembangan Bahan Ajar Teks Fabel dan Cerpen Berorientasi Soft Skill - Emah Khuzaemah; Hikmah Uswatun Ummi (Jurusan Tadris Bahasa Indonesia, 2019)
The low level of soft skills among employees, many complained by various companies and agencies. This study aims to develop fable and short story text teaching materials oriented to soft skills. Based on the results of the identification of 91% of informants agree that there are a fable and short story teaching materials that are oriented towards soft skills. Teaching materials developed titled Mari Menulis Fabel yang Inspiratif. Activities carried out include: develop your imagination, determine ideas and themes, draw characters and characters, arrange events and develop stories, complete stories meaningfully, and develop your inspiration.Â Masih rendahnya soft skill di kalangan karyawan, banyak dikeluhkan oleh berbagai perusahaan dan instansi. Penelitian ini bertujuan untuk mengembangkan bahan ajar teks fabel dan cerpen berorientasi soft skill. Berdasarkan hasil identifikasi 91% informan setuju adanya bahan ajar fabel dan cerpen yang berorientasi soft skill. Bahan ajar yang dikembangkan berjudul Mari Menulis Fabel yang Inspiratif. Kegiatan yang dilakukan, meliputi: kembangkan imajinasimu, tentukan ide dan tema, gambarkan tokoh dan karakternya, rangkai peristiwa dan kembangkan cerita, selesaikan cerita dengan penuh makna, dan kembangkan inspirasimu.